Soft magnetic metal powder, method for producing same, and resin composition

By using B-type reducing agent to treat Fe, Ni and Co metal salt aqueous solutions in the liquid phase reduction method, soft magnetic metal powder with uniform particle size distribution and not easy to condense was prepared, which solved the problem of insufficient magnetic characteristics of powder in the high-frequency band in the prior art, and achieved the preparation of high Q-value magnetic materials.

CN119866530APending Publication Date: 2025-04-22TODA KOGYO CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380062626.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-28
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the prior art, soft magnetic metal powders tend to form aggregates or uneven primary particle sizes in liquid phase reduction, resulting in the inability to obtain sufficient magnetic properties in high frequency bands.

Method used

By dropping the liquid phase reduction method of reducing liquid containing a B-based reducing agent into one or more metal brine solution selected from Fe, Ni and Co, a soft magnetic metal powder containing B of 5.0% by weight or more and 10.0% by weight or less was prepared, with an average primary particle size of 0.05 μm or more and 1.5 μm or less, and the coefficient of change and coagulation ratio are controlled within a suitable range to ensure that the powder is not easy to condense and the particle size distribution is uniform.

Benefits of technology

It realizes the difficulty of coagulation and uniform particle size of soft magnetic metal powder, improves the magnetic characteristics and Q value of magnetic materials in high frequency bands, and is suitable for small high-frequency sensors or noise suppression parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866530A_ABST
    Figure CN119866530A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing a soft magnetic metal powder which is a fine particle but not liable to agglomerate, has good dispersibility, is spherical, has excellent filling properties and dispersibility into a resin or the like, has a narrow particle size distribution range, has uniform primary particle diameter, and has excellent magnetic properties. As a result, it is possible to produce a magnetic material having excellent magnetic characteristics at a desired frequency and having a high Q value in a high-frequency band of 1 GHz or more. The solution of the present invention is a soft magnetic metal powder containing 5.0 wt% to 10.0 wt% of B, the remainder comprising one or more metals selected from Fe, Ni, and Co, the average primary particle diameter being 0.05 [mu] m to 1.5 [mu] m, the coefficient of change (standard deviation of primary particle diameter / average primary particle diameter) being 0.25 or less, and the average primary particle diameter being 0.5 [mu] m or less. The aggregation ratio (average aggregation particle diameter / average primary particle diameter) is 3 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a soft magnetic metal powder. Specifically, the soft magnetic metal powder is fine particles that are not easy to aggregate, has good dispersibility, is spherical, has excellent filling and dispersibility in resins, etc., and has a narrow particle size distribution range and a uniform primary particle size, so that a magnetic material with excellent magnetic properties at a desired frequency and a high Q value in a high frequency band above 1 GHz can be produced. Background Art

[0002] As various electrical devices become more sophisticated, smaller, and thinner, components such as inductors and transformers built into the electrical devices are being required to have improved magnetic properties and be thinner.

[0003] In addition, with the advancement of AI and automation of equipment, high-speed communication and high responsiveness are required, and the development of magnetic materials that can cope with high frequencies, such as sensors and noise suppression components, is sought.

[0004] In components used in high frequencies, especially GHz bands, it is sought to develop a magnetic material having a large Q value (Q value = μ′ / μ″), i.e., a ratio of the real part (μ′) of the permeability to the imaginary part (μ″).

[0005] In the past, the main magnetic material used for inductors was ferrite. However, in recent years, as the current in automation has increased, metal-based materials with higher saturation magnetic flux density have attracted attention.

[0006] In order to improve or stabilize the magnetic properties of magnetic materials such as inductors, fine magnetic powders with uniform particle size distribution are required.

[0007] If the aggregate is composed of soft magnetic metal powder particles having a uniform primary particle size and being unlikely to aggregate, it can be expected that the magnetic properties of the magnetic material will be improved and stabilized.

[0008] However, there is a problem that submicron-level particles are easily aggregated and therefore cannot be easily mixed into resin or the like.

[0009] As a method for producing fine-particle soft magnetic metal powder, there is a liquid phase reduction method described in Patent Document 1 described below.

[0010] However, the conventional liquid phase reduction method has problems such as the formation of agglomerates and non-uniform primary particle size.

[0011] Since the particle size distribution is closely related to the frequency characteristics, if the primary particle size is non-uniform and the particle size distribution is wide, there is a possibility that sufficient magnetic characteristics cannot be obtained in the desired high-frequency band.

[0012] Therefore, when used industrially, there is a problem that the aggregated particles need to be crushed or classified to remove metal fine particles having a primary particle size other than a desired one.

[0013] In methods such as atomization, carbonyl decomposition, and spray pyrolysis that do not involve a liquid phase reaction, there are also problems such as the formation of agglomerates or non-uniform primary particle sizes.

[0014] Therefore, there is a need to develop a soft magnetic metal powder which does not aggregate even in the form of fine particles and is easily dispersed, can be filled into resins and the like, and can produce a magnetic material having a uniform primary particle size and excellent magnetic properties at high frequencies.

[0015] Prior art literature

[0016] Patent Literature

[0017] Patent document 1: Japanese Patent Application Laid-Open No. 2010-261065. Summary of the invention

[0018] Problems to be solved by the invention

[0019] Patent document 1 describes a method for producing soft magnetic metal powder having a smaller particle size than before by a liquid phase reduction method in which a reducing solution containing a B (boron)-based reducing agent is dropped into an aqueous solution of an iron salt containing an iron salt, a chelating agent, a dispersant, a pH adjuster, and a P (phosphorus)-based reducing agent.

[0020] However, the production method described in Patent Document 1 has problems such as the formation of aggregates and non-uniform primary particle size.

[0021] The inventors of the present invention have repeatedly carried out multiple tentative trials / experiments with the goal of solving the above-mentioned problems as a technical issue, and as a result, obtained the following impressive knowledge, thereby completing the above-mentioned technical issue: a soft magnetic metal powder, which contains more than 5.0 wt% and less than 10.0 wt% B, and the remainder is composed of one or more metals selected from Fe (iron), Ni (nickel) and Co (cobalt), wherein the average primary particle size is more than 0.05 μm and less than 1.5 μm, the coefficient of variation (standard deviation of primary particle size / average primary particle size) is less than 0.25, and the agglomeration ratio (average agglomerated particle size / average primary particle size) is less than 3. If it is such a soft magnetic metal powder, although it is a microparticle, it is not easy to agglomerate, has good dispersibility and is spherical, so it has excellent filling properties. Moreover, since the particle size distribution is narrow and the primary particle size is uniform, it is possible to produce magnetic materials with excellent magnetic properties even in high-frequency bands.

[0022] Technical solutions to solve problems

[0023] The above technical problems can be solved by the following present invention.

[0024] The present invention is a soft magnetic metal powder, which contains more than 5.0 wt% and less than 10.0 wt% of B, and the remainder is composed of one or more metals selected from Fe, Ni and Co, wherein the average primary particle size is more than 0.05 μm and less than 1.5 μm, the coefficient of variation expressed by the following (Formula 1) is less than 0.25, and the agglomeration ratio expressed by the following (Formula 2) is less than 3.

[0025] (Formula 1) Standard deviation of primary particle size (σ) / average primary particle size (D1)

[0026] (Formula 2) Average agglomerated particle size (D2) / Average primary particle size (D1)

[0027] Furthermore, the present invention provides the soft magnetic metal powder having an O (oxygen) content of less than 8.0% by weight.

[0028] Furthermore, the present invention provides a resin composition containing the soft magnetic metal powder.

[0029] The present invention is also a method for producing the soft magnetic metal powder, wherein the powder is produced by a liquid phase reduction method in which a reducing solution containing a B-based reducing agent is dropped into an aqueous solution of a metal salt of one or more selected from Fe, Ni and Co.

[0030] Effects of the Invention

[0031] The present invention provides a soft magnetic metal powder which is fine particles but is not easily agglomerated, has excellent dispersibility, and has a uniform primary particle size, and therefore has excellent magnetic properties.

[0032] Since the range of the particle size distribution of the primary particle size is narrow, a high Q value is exhibited in a high frequency band of 1 GHz or more.

[0033] In addition, when the content of O is less than 8.0 wt %, a decrease in saturation magnetization due to the oxide film can be suppressed.

[0034] Furthermore, if the resin composition contains the soft magnetic metal powder of the present invention, a magnetic material having excellent magnetic properties can be produced.

[0035] In particular, since the soft magnetic metal powder in the present invention is a microparticle with an average primary particle size of 0.05 μm or more and 1.5 μm or less, the eddy current in the particles is reduced. The eddy current loss of the soft magnetic metal powder tends to increase in proportion to the square of the driving frequency, so it is effective in magnetic materials used in high frequency bands.

[0036] Therefore, the soft magnetic metal powder of the present invention can be suitably used in small high-frequency inductors and noise suppression parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a SEM photograph of the soft magnetic powder of Example 1 (10,000 times).

[0038] Figure 2 This is a SEM photograph of the soft magnetic powder of Example 2 (magnification 10,000). DETAILED DESCRIPTION

[0039] The soft magnetic metal powder in the present invention is an aggregate of fine particles having a narrow primary particle size distribution.

[0040] The average primary particle size of the soft magnetic metal powder in the present invention is preferably 0.05 μm to 1.5 μm, more preferably 0.07 μm to 1.0 μm.

[0041] This is because when the average primary particle size is less than 0.05 μm, the ratio of the oxide film on the particle surface increases, so the saturation magnetization decreases, and when it exceeds 1.5 μm, the eddy current loss at high frequency increases.

[0042] In order to suppress a decrease in saturation magnetization due to an oxide film, the content of O in the soft magnetic metal powder is preferably less than 8.0% by weight, more preferably 6.2% by weight or less.

[0043] The lower limit of the content of O in the soft magnetic metal powder is 0.05% by weight.

[0044] The coefficient of variation of the primary particle size of the soft magnetic metal powder in the present invention represented by (Formula 1) is preferably 0.25 or less, more preferably 0.23 or less, and even more preferably 0.16 or less.

[0045] (Formula 1) Standard deviation of primary particle size (σ) / average primary particle size (D1)

[0046] When the coefficient of variation exceeds 0.25, when applied to a small electronic component for high-frequency use, there is a possibility that a sufficient Q value cannot be obtained in a high-frequency band.

[0047] In addition, the lower limit of the coefficient of variation is approximately 0.001.

[0048] The aggregation ratio represented by (Formula 2) in the present invention is preferably 3 or less, more preferably 2.7 or less, and even more preferably 2.5 or less.

[0049] (Formula 2) Average agglomerated particle size (D2) / Average primary particle size (D1)

[0050] When the condensation ratio exceeds 3, when applied to a high-frequency small electronic component, there is a possibility that a sufficient Q value cannot be obtained in a high-frequency band.

[0051] On the other hand, when the aggregation ratio exceeds 3, there is a possibility that the dispersibility into resin or the like is reduced.

[0052] In addition, in fine particles with uniform particle sizes and little aggregation, the aggregation ratio may be lower than 1.

[0053] The lower limit of the aggregation ratio in the present invention is about 0.3.

[0054] The primary particle size of the soft magnetic metal powder can be measured by photographing the powder at 2000 to 10000 times using a scanning microscope (SEM) and then using image analysis software.

[0055] The content of B contained in the soft magnetic metal powder of the present invention is preferably 5.0 to 10.0% by weight, more preferably 5.2 to 9.0% by weight, and further preferably 5.8 to 8.0% by weight.

[0056] When the B content is more than 10.0 wt %, the ratio of the magnetic element decreases, so the saturation magnetization (σs) decreases, and there is a possibility that sufficient magnetism cannot be obtained.

[0057] On the other hand, when the B content is less than 5.0% by weight, the B material becomes a crystalline material, so that the eddy current loss at a high frequency may increase.

[0058] Furthermore, in the production method based on the liquid phase reduction method, if a composition having a B-based reducing action is not used, the number of non-spherical fine particles increases, and thus the magnetic properties in the desired high frequency band may be degraded.

[0059] The shape of the soft magnetic metal powder is not particularly limited, but is preferably spherical from the viewpoint of improving dispersibility or filling properties in resins and the like.

[0060] The σs of the soft magnetic metal powder is preferably 120 Wb·m / kg or more, more preferably 130 Wb·m / kg or more, and even more preferably 140 Wb·m / kg or more.

[0061] The coercive force (Hc) is preferably 10 kA / m or less, more preferably 5 kA / m or less, and further preferably 3 kA / m or less.

[0062] The soft magnetic metal powder in the present invention may be coated with a metal oxide, because this is expected to improve the insulation effect.

[0063] Next, a method for producing the soft magnetic metal powder according to the present invention will be described.

[0064] The soft magnetic metal powder in the present invention can be produced by a liquid phase reduction method in which an aqueous solution of one or more metal salts selected from the group consisting of Fe, Ni and Co is reduced with a B-based reducing agent.

[0065] Examples of the iron salt include iron (II) sulfate, iron (II) chloride, iron (II) acetate, iron (II) oxalate, iron (III) chloride, and iron (III) sulfate, but are not limited thereto.

[0066] Examples of the nickel salt include nickel (II) chloride, nickel (II) sulfate, nickel (II) nitrate, and nickel (III) fluoride, but are not limited thereto.

[0067] Examples of the cobalt salt include cobalt (II) chloride, cobalt (II) sulfate, and cobalt (II) nitrate, but are not limited thereto.

[0068] The aqueous metal salt solution may contain a complexing agent or a reducing agent other than the B-based reducing agent.

[0069] The complexing agent is not particularly limited, and examples thereof include glycine, alanine, ammonium sulfate, ammonium chloride, and trisodium citrate.

[0070] The reducing agent other than the B-based reducing agent is not particularly limited, and a P-based reducing agent may also be used.

[0071] Examples of the P-based reducing agent include sodium hypophosphite and calcium hypophosphite, but are not limited thereto.

[0072] The aqueous metal salt solution does not necessarily need to contain a P-based reducing agent.

[0073] The P content of the soft magnetic metal powder of the present invention is preferably 2.0 wt% or less. If it exceeds 2.0 wt%, the proportion of magnetic elements decreases, so σs decreases, and sufficient magnetic properties may not be obtained.

[0074] The metal salt aqueous solution is preferably adjusted to pH 6.5 to 11.0 using a pH adjuster.

[0075] The pH adjuster is not particularly limited, and examples thereof include sodium hydroxide, aqueous ammonia, and sodium hydrogen carbonate.

[0076] The aqueous metal salt solution may appropriately contain a dispersant, a catalyst, and a defoaming agent.

[0077] The reducing agent for reducing the aqueous metal salt solution is a B-series reducing agent.

[0078] Examples of the B-based reducing agent include sodium borohydride, potassium borohydride, and dimethylaminoborane.

[0079] It is also possible to use hydrazine containing no B together with the B-based reducing agent.

[0080] The amount of the B-based reducing agent added is preferably 15 to 60% by weight based on the weight of the metal salt.

[0081] When the amount of the B-based reducing agent added is less than 15 wt%, it will become a crystalline substance, so the eddy current loss at high frequencies may increase. When it exceeds 60 wt%, the proportion of magnetic elements decreases, so σs becomes low and sufficient magnetic properties may not be obtained.

[0082] The reduction temperature is preferably 10°C to 95°C.

[0083] When the reduction temperature is lower than 10°C, the particle size becomes larger and the desired size cannot be obtained. In addition, the cooling cost increases, which is not industrially preferable. When the reduction temperature is higher than 95°C, the deactivation of the reducing agent becomes faster, so the soft magnetic metal powder of the present invention may not be obtained.

[0084] The soft magnetic metal powder in the present invention can be mixed with a resin to form a resin composition.

[0085] The resin composition can be used to produce magnetic materials such as inductors and magnetic sheets.

[0086] The type of resin is not particularly limited and may be appropriately selected depending on the intended use or required heat resistance.

[0087] Examples of the resin include thermoplastic resins such as epoxy resins, phenolic resins, silicone resins, polyamide-imide resins, unsaturated polyester resins, diallyl phthalate resins, xylene resins, polyester resins, polyvinyl chloride resins, polyvinyl butyral resins, polyamino resins, cellulose resins, nitrile-butadiene rubbers, styrene-butadiene rubbers, and styrene-butadiene rubbers; and thermosetting resins such as epoxy resins, phenolic resins, amide resins, and imide resins.

[0088] The content of the soft magnetic metal powder in the resin composition is not particularly limited, and can be appropriately varied according to desired physical properties such as flexibility and desired magnetic properties such as Q value, but is preferably 10% to 90% by volume, more preferably 15% to 85% by volume, and further preferably 20% to 80% by volume.

[0089] The higher the Q value of the resin composition containing the soft magnetic metal powder, the higher the electrical efficiency can be, which is preferred.

[0090] The Q value of the resin composition at 1 GHz is preferably 5 or more, more preferably 7 or more, and even more preferably 10 or more. The resin composition containing the soft magnetic metal powder of the present invention can also achieve a Q value of 10 or more.

[0091] This is because by highly filling fine particles having high magnetic properties, the product of the Q value and √(D1) increases, and thus properties suitable as a magnetic material for high-frequency use can be expected.

[0092] The Q value×√(D1) is preferably 5 or more, more preferably 6 or more, and further preferably 7 or more at 1 GHz.

[0093] Example

[0094] Although the present invention is described with reference to Examples and Comparative Examples, the present invention is not limited thereto.

[0095] (Example 1)

[0096] Iron (II) sulfate heptahydrate, glycine, and sodium hypophosphite are placed in a glass beaker together with 600 ml of distilled water in a manner such that the concentrations of iron (II) sulfate heptahydrate, glycine, and sodium hypophosphite are 0.20 mol / l, 0.10 mol / l, and 0.20 mol / l, and the mixture is stirred at room temperature at 100 rpm to 300 rpm using a stirrer while adjusting the pH to 7.5 to 9.5 using sodium hydroxide to prepare a metal salt aqueous solution.

[0097] Sodium borohydride was mixed with 200 ml of distilled water so as to have a concentration of 0.50 mol / l, and dissolved by stirring at 100 to 300 rpm with a stirrer at room temperature to prepare a reducing solution.

[0098] In a nitrogen atmosphere, the reducing solution was dropped into a 50° C. aqueous metal salt solution stirred at 100 rpm to 300 rpm by a stirrer.

[0099] The point in time when the foaming of the metal salt aqueous solution disappears was regarded as the end point of the reduction reaction.

[0100] After the reduction reaction was completed, the mixture was washed with distilled water, replaced with ethanol, and then dried in a nitrogen inert atmosphere to obtain a soft magnetic metal powder.

[0101] (Example 2)

[0102] Iron (II) sulfate heptahydrate, glycine, ammonium sulfate, and sodium hypophosphite are added into a glass beaker together with 600 ml of distilled water in a manner such that the concentrations are 0.20 mol / l of iron (II) sulfate heptahydrate, 0.10 mol / l of glycine, 0.20 mol / l of ammonium sulfate, and 0.20 mol / l of sodium hypophosphite, and the mixture is stirred at room temperature at 100 rpm to 300 rpm using a stirrer while adjusting the pH to 9.0 to 11.0 using sodium hydroxide to prepare a metal salt aqueous solution.

[0103] Sodium borohydride was mixed with 200 ml of distilled water so as to have a concentration of 0.30 mol / l, and dissolved by stirring at 100 to 300 rpm with a stirrer at room temperature to prepare a reducing solution.

[0104] The reducing solution was added dropwise to a 25° C. aqueous metal salt solution stirred at 100 rpm to 300 rpm by a stirrer in a nitrogen atmosphere.

[0105] The point in time when the foaming of the metal salt aqueous solution disappears was regarded as the end point of the reduction reaction.

[0106] After the reduction reaction was completed, the mixture was washed with distilled water, replaced with ethanol, and then dried in a nitrogen inert atmosphere to obtain a soft magnetic metal powder.

[0107] (Example 3)

[0108] Iron (II) sulfate heptahydrate and ammonium sulfate were added to a glass beaker together with 400 ml of distilled water in such a manner that the concentrations of iron (II) sulfate heptahydrate and ammonium sulfate were 0.21 mol / l and 0.58 mol / l, respectively, and the mixture was stirred at room temperature at 100 rpm to 300 rpm using a stirrer while adjusting the pH to 9.0 to 11.0 using sodium hydroxide to prepare a metal salt aqueous solution.

[0109] Sodium borohydride was mixed with 400 ml of distilled water so as to have a concentration of 0.22 mol / l, and dissolved by stirring at 100 to 300 rpm with a stirrer at room temperature to prepare a reducing solution.

[0110] The reducing solution was added dropwise to a 25° C. aqueous metal salt solution stirred at 100 rpm to 300 rpm by a stirrer in a nitrogen atmosphere.

[0111] The point in time when the foaming of the metal salt aqueous solution disappears was regarded as the end point of the reduction reaction.

[0112] After the reduction reaction was completed, the mixture was washed with distilled water, replaced with ethanol, and then dried in a nitrogen inert atmosphere to obtain a soft magnetic metal powder.

[0113] (Comparative Example 1)

[0114] According to the method disclosed in Patent Document 1, iron (II) chloride hydrate, ammonium chloride, trisodium citrate hydrate, polyvinyl pyrrolidone, and sodium hypophosphite hydrate are added together with 200 ml of distilled water in such a manner that the concentrations of iron (II) chloride hydrate are 1.0 mol / l, ammonium chloride is 1.5 mol / l, trisodium citrate hydrate is 0.8 mol / l, polyvinyl pyrrolidone is 0.004 mol / l, and sodium hypophosphite hydrate is 1.5 mol / l. The mixture is stirred at room temperature at 160 rpm to 300 rpm by a stirrer while adjusting the pH to 10 using a 30% sodium hydroxide aqueous solution to prepare a metal salt aqueous solution.

[0115] Sodium borohydride was mixed with 150 ml of distilled water so as to have a concentration of 0.50 mol / l, and dissolved by stirring at 160 to 300 rpm with a stirrer at room temperature to prepare a reducing solution.

[0116] The reducing liquid was dropped into a 25° C. aqueous metal salt solution stirred at 160 rpm to 300 rpm by a stirrer.

[0117] The point in time when the foaming of the metal salt aqueous solution disappears was regarded as the end point of the reduction reaction.

[0118] After the reduction reaction was completed, the mixture was washed with distilled water, replaced with ethanol, and then dried in a nitrogen inert atmosphere to obtain a soft magnetic metal powder.

[0119] (Comparative Example 2)

[0120] Iron (II) sulfate heptahydrate and ammonium sulfate were added to a glass beaker together with 400 ml of distilled water in such a manner that the concentrations of iron (II) sulfate heptahydrate and ammonium sulfate were 0.21 mol / l and 1.93 mol / l, respectively, and the mixture was stirred at room temperature at 100 rpm to 300 rpm using a stirrer while adjusting the pH to 9.0 to 11.0 using sodium hydroxide to prepare a metal salt aqueous solution.

[0121] Sodium borohydride was mixed with 400 ml of distilled water so as to have a concentration of 0.22 mol / l, and dissolved by stirring at 100 to 300 rpm with a stirrer at room temperature to prepare a reducing solution.

[0122] The reducing solution was added dropwise to a 20° C. aqueous metal salt solution stirred at 100 rpm to 300 rpm by a stirrer in a nitrogen atmosphere.

[0123] The point in time when the foaming of the metal salt aqueous solution disappears was regarded as the end point of the reduction reaction.

[0124] After the reduction reaction was completed, the mixture was washed with distilled water, replaced with ethanol, and then dried in a nitrogen inert atmosphere to obtain a soft magnetic metal powder.

[0125] The crystal structure of each of the obtained soft magnetic metal powders was evaluated using an X-ray diffraction apparatus, and it was confirmed that the powder was amorphous.

[0126] A silicone resin sheet containing 32 volume % of the soft magnetic metal powder obtained in Example 1 and a resin sheet containing 40 volume % of each soft magnetic metal powder obtained in Examples 2, 3 and Comparative Examples 1 and 2 were prepared, and the Q value at 1 GHz was evaluated using a magnetic permeability measuring system.

[0127] (Determination of primary particle size and average primary particle size)

[0128] Using a scanning electron microscope, images were taken at 2000 to 10000 times magnification, and the longest diameter of all particles in the photographed field of view was measured using image analysis software Image-kun (manufactured by Asahi Kasei Engineering Corporation), and the average primary particle size (D1) was calculated. Furthermore, the standard deviation (σ) of the primary particle size was calculated.

[0129] In addition, the coefficient of variation is calculated according to (Formula 1) based on the obtained D1 and σ.

[0130] (Formula 1) Standard deviation of primary particle size (σ) / average primary particle size (D1)

[0131] (Measurement of average agglomerated particle size)

[0132] The average aggregate particle size (D2) was measured using a particle size distribution analyzer (Microtrac MT3300EXII, manufactured by MicrotracBEL Co., Ltd.) The measurement range was 0.02 μm to 2000 μm, and alcohol was used as a solvent.

[0133] The aggregation ratio was calculated according to (Formula 2) from the obtained D2 and D1.

[0134] (Formula 2) Average agglomerated particle size (D2) / Average primary particle size (D1)

[0135] (Crystal Structure)

[0136] The crystal phase in the sample was identified by measuring using an X-ray diffraction apparatus (D8 ADVANCE, manufactured by BRUKER Japan Ltd.).

[0137] (Component Analysis<Fe, P>)

[0138] The measurement was performed using an X-ray fluorescence diffraction apparatus (ZSX PrimusII, manufactured by Rigaku Corporation) in accordance with the "General Rules for X-ray Fluorescence Analysis" of JIS K0119.

[0139] (Component Analysis)

[0140] The measurement was performed using an inductively coupled plasma (ICP) emission spectrometer (iCAP6500 / manufactured by Thermo Fisher Scientific).

[0141] (Component Analysis<O>)

[0142] The measurement was performed using an oxygen, nitrogen and hydrogen analyzer (EMGA-930 / manufactured by Horiba, Ltd.).

[0143] (Magnetic properties<Saturation magnetization (σs) and coercive force (Hc)>)

[0144] The saturation magnetization (σs) and coercive force (Hc) of the soft magnetic metal powders of Examples and Comparative Examples were measured using a vibrating sample magnetometer (VSM) (TM-VSM2130MRHL model / manufactured by Tamagawa Seisakusho Co., Ltd.).

[0145] (Magnetic properties<Material constants (μ′, μ″)>)

[0146] For the sheet-like molded products (resin sheets) of each soft magnetic metal powder of the embodiments and comparative examples containing 30 volume % to 40 volume % in silicone resin (X-32-2100-T / manufactured by Shin-Etsu Chemical Co., Ltd.), the real part μ′ and the imaginary part μ″ of the permeability were measured at 0.1 GHz to 10 GHz using a permeability measuring system (N5230A / manufactured by Agilent Technologies, Inc.), and the Q value was calculated based on the ratio of the real part of the permeability (μ′) / the imaginary part of the permeability (μ″) at 1 GHz.

[0147] Table 1 shows the materials and conditions used in Examples and Comparative Examples, and Table 2 shows the results.

[0148] In Table 2, σ represents the standard deviation of particle diameter, D1 represents the average primary particle diameter, and D2 represents the average aggregated particle diameter.

[0149] The scanning electron microscope (SEM) images (10000 times) of the spherical soft magnetic metal powders obtained in Example 1 and Example 2 are shown in Figure 1 and Figure 2 .

[0150] [Table 1]

[0151]

[0152] [Table 2]

[0153]

[0154] From Table 2, Figure 1 and Figure 2 It has been demonstrated that the soft magnetic metal powder of the present invention is spherical, has a uniform primary particle size, is not easily agglomerated, and can produce a magnetic material having excellent magnetic properties at high frequencies.

[0155] Industrial Applicability

[0156] The soft magnetic metal powder in the present invention is a microparticle that is not easy to agglomerate, has good dispersibility, is spherical, and has a narrow range of particle size distribution and a uniform primary particle size. Therefore, it is possible to produce magnetic materials with high Q values ​​in high frequency bands above 1 GHz. Therefore, it is suitable for use in electronic components such as sensors with excellent magnetic properties in high frequency bands above 1 GHz.

[0157] Therefore, the present invention has high industrial applicability.

Claims

1. A soft magnetic metal powder, comprising 5.0 wt% or more and 10.0 wt% or less of B, the remainder of which is composed of one or more metals selected from Fe, Ni and Co, wherein: The average primary particle size is 0.05 μm or more and 1.5 μm or less, the coefficient of variation expressed by the following formula 1 is 0.25 or less, the aggregation ratio expressed by the following formula 2 is 3 or less, Formula 1: Standard deviation of primary particle size / average primary particle size, Formula 2: Average agglomerated particle size / average primary particle size.

2. The soft magnetic metal powder according to claim 1, wherein The content of O was less than 8.0% by weight.

3. A resin composition comprising the soft magnetic metal powder according to claim 1 or 2.

4. A method for producing a soft magnetic metal powder according to claim 1 or 2, wherein: The production is carried out by a liquid phase reduction method in which a reducing solution containing a B-based reducing agent is dropped into an aqueous solution of a metal salt of one or more selected from Fe, Ni and Co.

Citation Information

Patent Citations

  • Amorphous soft magnetic alloy powder, dust core and inductor

    JP2010261065A